2016
DOI: 10.1161/circresaha.115.306529
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Sensor EPAC Proteins and Their Role in Cardiovascular Function and Disease

Abstract: C yclic adenosine 3′,5′-monophosphate (cAMP) is one of the most studied signaling molecules that plays a critical role in cellular responses to extracellular stimuli in the cardiovascular system. It controls a wide range of biological effects, including cell proliferation, differentiation, and apoptosis. 1 cAMP is produced from ATP by transmembrane adenylyl cyclase on activation of Gs-coupled G protein-coupled receptors. 2In addition, soluble adenylyl cyclase is a second intracellular source of cAMP and can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
145
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 149 publications
(237 reference statements)
1
145
0
Order By: Relevance
“…42 Although these findings seem contradictory, Epac signaling is spatially and temporally regulated by diverse anchoring mechanisms that control specific functions of this cAMP-sensitive guanine exchange factor by recruitment to distinct subcellular localizations. 37 We, therefore, speculate that cell type-specific signals contribute to differential effect of Epac on mitochondrial ROS production.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…42 Although these findings seem contradictory, Epac signaling is spatially and temporally regulated by diverse anchoring mechanisms that control specific functions of this cAMP-sensitive guanine exchange factor by recruitment to distinct subcellular localizations. 37 We, therefore, speculate that cell type-specific signals contribute to differential effect of Epac on mitochondrial ROS production.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, Epac proteins exert their biological function in combination with scaffolding proteins, such as β-arrestin, cAMP phosphodiesterases that regulates the duration and intensity of cAMP signaling, and PKA. 36,37 Because various mitochondrial compartments contain these proteins that are able to sense or respond to cAMP and may have antagonistic outputs, 2 further studies are needed to identify the multimolecular complexes that affect cAMP-Epac1 signaling and Epac1 mitochondrial function in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, even with these controversial results over the hypertrophic signaling of EPAC, EPAC-null hearts appear to be protected against many stress-induced myopathies and arrhythmias (785,819). Extensive effort has been invested into the determination of the EPAC-mediated signaling mechanisms in cardiomyopathies, arrhythmias, and heart failure which has been meticulously reviewed recently by two independent groups (320,601). Rather than redundantly reviewing these functions of EPAC, we refer the reader to these excellent reviews, and will instead focus on more recently identified roles for EPACs in vascular disease progression.…”
Section: Cardiomyopathiesmentioning
confidence: 99%
“…Indeed, there is a growing body of evidence showing that Rac1 protects the EC barrier, at least in part, via an Epac1‐Rap1 mediated signaling pathway (Aslam et al, ; Baumer, Spindler, Werthmann, Bunemann, & Waschke, ; Birukova et al, ). Activation of Epac‐Rap1 by its agonists enhances EC barrier function, reduces the destructive effects of inflammatory mediators on EC permeability and promotes cell junction stability (Cullere et al, ; Kooistra et al, ; Lezoualc'h, Fazal, Laudette, & Conte, ). Rap1‐mediated Rac1 activation may involve Rho A inhibition through activation of ARAP3, Rap‐dependent RhoGAP (Jeon et al, ; Jeon, Kim, Lee, et al, ; Jeon, Kim, Morii, et al, ).…”
Section: Discussionmentioning
confidence: 99%